Trajectories of Blood Pressure in Patients with Established Coronary Artery Disease over 20 years - Piotr Jankowski; Paweł Kozieł; Grzegorz Bilo; Jarosław Pinkas; Danuta Czarnecka; Kalina Kawecka-Jaszcz; Andrzej Pająk (International Journal of Hypertension)
Objective. To evaluate changes in blood pressure (BP) values in patients with established coronary artery disease (CAD) over 20 years (1997–2017). Materials and Methods. Consecutive patients aged <71 years and hospitalized for acute coronary syndrome or myocardial revascularization procedures were recruited and interviewed 6–18 months after their discharge from the hospital. BP was measured in 1997–1998, 1999–2000, 2006–2007, 2011–2013, and 2016–2017. The same five hospitals took part in the surveys at each time point. Results. We examined 412 patients in 1997–1998, 427 in 1999–2000, 422 in 2006–2007, 462 in 2011–2013, and 272 in 2016–2017. The proportion of patients with BP at the recommended goal was 49.2% in 1997–98, 44.5% in 1999–2000, 44.7% in 2006–07, 51.1% in 2011–13, and 58.8% in 2016–17 (p<0.001). Mean systolic and diastolic BP decreased significantly independent of age, sex, and education (systolic BP: 137.9 ± 21.4 mmHg in 1997–98, 139.5 ± 21.6 mmHg in 1999–2000, 136.1 ± 20.3 mmHg in 2006–07, 134.8 ± 22.0 mmHg in 2011–13, and 134.2 ± 18.6 mmHg in 2016–17, p<0.001; diastolic BP: 83.4 ± 11.0 mmHg in 1997–98, 84.8 ± 12.0 mmHg in 1999–2000, 85.2 ± 11.0 mmHg in 2006–07, 80.9 ± 12.5 mmHg in 2011–13, and 81.1 ± 10.4 mmHg in 2016–17; p<0.001). Conclusion. The analysis of five multicenter surveys provides evidence of a decrease in BP in patients with established CAD over two decades. This trend is independent of age, sex, and the education level of the patients.